Influence of glacier inventories on ice thickness estimates and future glacier change projections in the Tian Shan range, Central Asia - Fei Li; Fabien Maussion; Guangjian Wu; Wenfeng Chen; Zhengliang Yu; Yaojun Li; Guohua Liu (Journal of Glaciology, 2023)
The Tian Shan mountain range, known as the water towers of Central Asia, plays a key role in local water supply, yet large uncertainties remain about the amount of water that is stored in its glaciers. In this study, we assess the impact of the boundary conditions on ice thickness estimates using two inversion models: a mass conservation (MC) model and a basal shear stress (BS) model. We compare the widely used Randolph Glacier Inventory version 6 with the updated Glacier Area Mapping for Discharge from the Asian Mountains glacier inventory, as well as two digital elevation models (SRTM DEM and Copernicus DEM). The results show that the ice volume (in ~2000 CE) in the Tian Shan range is 661.0 ± 163.5 km3 for the MC model and 552.8 ± 85.3 km3 for the BS model. There are strong regional differences due to inventory, especially for glaciers in China (17–25%). However, the effect of different DEM sources on ice volume estimation is limited. By the end of the 21st century, the projected mass loss differences between inventories are higher than between adjacent emission scenarios, illustrating the vital importance of high-quality inventories. These differences should be carefully considered during water resource planning.